Antibody‐dependent enhancement (ADE) of SARS‐CoV‐2 in patients exposed to MERS‐CoV and SARS‐CoV‐2 antigens - Swapna Thomas (17337925) (2024)
This study evaluated the potential for antibody‐dependent enhancement (ADE) in serum samples from patients exposed to Middle East respiratory syndrome coronavirus (MERS‐CoV). Furthermore, we evaluated the effect of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccination on ADE in individuals with a MERS infection history. We performed ADE assay in sera from MERS recovered and SARS‐CoV‐2‐vaccinated individuals using BHK cells expressing FcgRIIa, SARS‐CoV‐2, and MERS‐CoV pseudoviruses (PVs). Further, we analyzed the association of ADE to serum IgG levels and neutralization. Out of 16 MERS patients, nine demonstrated ADE against SARS‐CoV‐2 PV, however, none of the samples demonstrated ADE against MERS‐CoV PV. Furthermore, out of the seven patients exposed to SARS‐CoV‐2 vaccination after MERS‐CoV infection, only one patient (acutely infected with MERS‐CoV) showed ADE for SARS‐CoV‐2 PV. Further analysis indicated that IgG1, IgG2, and IgG3 against SARS‐CoV‐2 S1 and RBD subunits, IgG1 and IgG2 against the MERS‐CoV S1 subunit, and serum neutralizing activity were low in ADE‐positive samples. In summary, samples from MERS‐CoV‐infected patients exhibited ADE against SARS‐CoV‐2 and was significantly associated with low levels of neutralizing antibodies. Subsequent exposure to SARS‐CoV‐2 vaccination resulted in diminished ADE activity while the PV neutralization assay demonstrated a broadly reactive antibody response in some patient samples. Other Information Published in: Journal of Medical Virology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jmv.29628